A legislative history of the fishery conservation and management act of 1976 : (U.S. Goverment Printing Office, 1976)
Contents: public law 94-265, the fishery conservation and management act of 1976; Senate debates and passage of H. R. 200; Senate reports and memorandums on S.961;...